Ethnomatology Study on the Structure of Historical Ornam Translateents of Maimun Palace - Saputra, Dwicahyo (JMEA : Journal of Mathematics Education and Application, 2024)
Ethnomathematics strengthens the relationship between mathematics and culture. The concept and culture of mathematics are inevitable in everyday life. Castles can serve as symbolic representations of certain cultural contexts. The Maimun Royal Palace is an example of how the city of Medan is represented culturally. This paper examines and analyzes the mathematical component of the Maimun Palace's ethnographic method for qualitative descriptive research. According to research, this method aims to provide a comprehensive explanation of all mathematical concepts contained in the Maimun Palace. Bishop's important actions at the Maimun Court demonstrate these mathematical concepts and components. The three main objectives of this research are as follows: (1) collecting and reviewing relevant literature; (2) providing an explanation of the results; and (3) provide an explanation of specific aspects of Bishop's mathematics. Today, flat shapes such as triangles and semicircles are used, along with the mathematical concepts of symmetry and geometric transformation, in carving motifs; The majority of geometric patterns and ornaments in this traditional house are in the form of squares, rectangles, rhombuses, and triangles.